Rivers of sunlight : how the sun cycles water around the earth - Bang, Molly; Chisholm, Penny (Bang, Molly. Sunlight series., 2016)
"The sun explains its role in the movement of water around the Earth, from the lifting of fresh water from the seas, to the movement of underwater currents that nourish the world's oceans. The sun has a hand in moving rivers of water in its liquid, gaseous, and solid states all around the Earth, enabling life to exist on our planet. But human beings are interfering in this natural cycle, unbalancing the amount of fresh water available."--